WAYS TO DIVERSIFY LOCAL BUDGET REVENUES - Matqurbonova Dilrabo Jumanazarovna (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2026)
This article analyzes ways and mechanisms for diversifying local budget revenues based on Uzbekistan's experience and international practice.